Effects of increased ambient temperature and supplemental altrenogest before pregnancy establishment in gilts. (8th January 2022) - Romoser, Matthew R; Bidne, Katie L; Baumgard, Lance H; Keating, Aileen F; Ross, Jason W
Abstract: Heat stress (HS ) mitigation strategies are critically needed to combat the substantial economic effects on animal agriculture. The manifestations of seasonal infertility include delayed puberty onset, reduced conception rates, decreased litter size, and increased wean to estrus interval. To assess the effects of HS during early gestation and evaluate the benefit of supplemental altrenogest (ALT ) as a mitigation strategy, 30 crossbred postpubertal gilts (157 ± 11 kg body weight) were subjected to estrous synchronization via 14 d oral administration of ALT. Artificial insemination during estrus was performed, and gilts were then placed into one of four treatment groups: HS (35 ± 1 °C for 12 h/31.60 ± 1 °C for 12 h) with (HSALT, n = 7) or without (HSCON, n = 7) 15 mg/d ALT supplementation or thermal neutral (TN ; 20 ± 1 °C) conditions with (TNALT, n = 8) or without (TNCON, n = 8) 15 mg/d ALT supplementation until 12 d post-estrus (dpe ). Administrating ALT occurred at 0600 hours from 3 to 12 dpe, and rectal temperatures (T R ) and respiration rates (RR ) were recorded. Blood was collected via jugular venipuncture on 0, 4, 8, and 12 dpe. Gilts were euthanized humanely at 12 dpe followed by the collection of ovarian tissue, and uterine flushing for conceptus collection. In HS compared with TN gilts, RR and TR were increased ( P < 0.01) but unaffected by ALT supplementation. Feed intake was reduced ( P < 0.01) by HS but unaltered by the ALT treatment. Corpora lutea (CL ) weight was reduced ( P < 0.01) in HSCON gilts when compared with TNCON and HSALT gilts despite progesterone concentrations in serum and luteal tissue not being affected by treatment ( P ≥ 0.10). CL diameter was reduced ( P ≤ 0.05) in HSALT gilts compared with other treatments. Interleukin-1β (IL1B ) uterine flush concentration was not affected ( P > 0.20) by environment or ALT supplementation, although moderate ( P = 0.06) interaction between environment and ALT existed, as IL1B concentration in TNALT was increased ( P = 0.03) compared with TNCON gilts. While environment did not affect conceptus development ( P = 0.90), ALT supplementation advanced conceptus elongation ( P < 0.01). Collectively, these data demonstrate that HS may affect luteal development before pregnancy establishment, and ALT increases conceptus elongation by 12 dpe.